Transformer‐less unified power flow controller in medium voltage distribution networks. Issue 6 (3rd March 2023) - Abdelrahman, Mohamed A.; Wang, Sheng; Ming, Wenlong; Wu, Jianzhong; Jenkins, Nick
Abstract: A transformer‐less unified power flow controller (UPFC) is a power electronic device consisting of series and shunt voltage source converters (VSCs) that are not connected to a common DC bus. It can control power flow in medium voltage (MV) distribution networks without the need for interfacing transformers. Hence there is a significant reduction in size and cost compared to a conventional UPFC. This paper investigates the operating range of a transformer‐less UPFC in an MV distribution network and the required power ratings of the series and shunt converters. The results showed that a transformer‐less UPFC is able to provide active power control using partially rated converters. However, its ability to control reactive power is limited by the current ratings of the converters. The analysis was verified using software simulation and hardware experiment. Abstract : The main advantage of a transformer‐less UPFC over a conventional UPFC is the complete removal of interfacing transformers, hence a significant reduction in its size and cost. The paper investigates the use of a transformer‐less UPFC in distribution networks, for example, the operating range of a transformer‐less UPFC and the required power ratings of the converters.